EXTRAÇÃO DE INFORMAÇÕES LÓGICO-CONCEITUAIS DE DICIONÁRIOS PARA A ELABORAÇÃO DE LÉXICOS COMPUTACIONAIS - Di Felippo, Ariani; Dias-Da-Silva, Bento Carlos (Intercâmbio, 2010)
The paper focuses on the description of the process of “mining” lexical semantic information from published dictionaries of Brazilian Portuguese language. Specifically, it is described the manual approach of compiling and filtering hyperonymy/hyponymy and holonymy/meronym logic-conceptual relations of concrete nouns. These relations, filtering from the dictionaries, will be use to organize part of the nouns of Wordnet.Br lexical database.